Kesalahan Calon Guru Matematika Dalam Mengembangkan Modul Ajar Jenjang Sekolah Menengah - Prayitno, Lydia Lia; Mutianingsih, Ninik; Lestari, Dea Ayu; Rosyidah, Annisa Dewi Ainur; Sumianto, Dadang (Universitas Dr. Soetomo, 2023)
Teachers are educators who are required to have pedagogical, professional, social, and personality competencies. The role of educational institutions prepares prospective teachers to have these competencies. This paper is a descriptive study involving 25 prospective mathematics teachers who program field experience courses in schools. This course requires a prospective teacher to develop mathematics teaching modules for the high school level. So, the purpose of this study describes the mistakes of prospective mathematics teachers in developing mathematics teaching modules. The data is collected through the documentation by collecting mathematics teaching modules developed by the prospective teachers, and then analyzed based on three components, such are general information, core information, and attachments. The results of this study indicate that the mistakes made by prospective teachers in the general information component happen in determining the model, approach, learning method, diagnostic results, time duration, and meetings assigned. Then, the mistakes in core components happen when prospective teachers determine meaningful understanding, triggering questions, designing assessments, not explaining learning syntax, scientific approach, 21st-century skills, Pancasila student profiles, and differentiation. Furthermore, in the attachment component, the mistakes happen in the development of LKPD which is not yet constructivist and can be done individually, has not developed appropriate learning media, has not been appropriate in developing remedial and enrichment programs, and has not written glossarial in mathematics teaching module. Keywords: mistakes, development, teaching module, Merdeka curriculum